Review of recent progresses on flexible oxide semiconductor thin film transistors based on atomic layer deposition processes *Project supported by the National Research Foundation of Korea (NRF) (No. NRF-2017R1D1A1B03034035), the Ministry of Trade, Industry & Energy (No. #10051403), and the Korea Semiconductor Research Consortium. (January 2018) - Sheng, Jiazhen; Han, Ki-Lim; Hong, TaeHyun; Choi, Wan-Ho; Park, Jin-Seong
Abstract: The current article is a review of recent progress and major trends in the field of flexible oxide thin film transistors (TFTs), fabricating with atomic layer deposition (ALD) processes. The ALD process offers accurate controlling of film thickness and composition as well as ability of achieving excellent uniformity over large areas at relatively low temperatures. First, an introduction is provided on what is the definition of ALD, the difference among other vacuum deposition techniques, and the brief key factors of ALD on flexible devices. Second, considering functional layers in flexible oxide TFT, the ALD process on polymer substrates may improve device performances such as mobility and stability, adopting as buffer layers over the polymer substrate, gate insulators, and active layers. Third, this review consists of the evaluation methods of flexible oxide TFTs under various mechanical stress conditions. The bending radius and repetition cycles are mostly considering for conventional flexible devices. It summarizes how the device has been degraded/changed under various stress types (directions). The last part of this review suggests a potential of each ALD film, including the releasing stress, the optimization of TFT structure, and the enhancement of device performance. Thus, the functional ALD layers in flexible oxide TFTs offer great possibilities regarding anti-mechanical stress films, along with flexible display and information storage application fields.